A biomimetic underwater vehicle actuated by waves with ionic polymer–metal composite soft sensors. (28th September 2015) - Shen, Qi; Wang, Tianmiao; Kim, Kwang J
Abstract: The ionic polymer–metal composite (IPMC) is a soft material based actuator and sensor and has a promising potential in underwater application. This paper describes a hybrid biomimetic underwater vehicle that uses IPMCs as sensors. Propelled by the energy of waves, this underwater vehicle does not need an additional energy source. A physical model based on the hydrodynamics of the vehicle was developed, and simulations were conducted. Using the Poisson–Nernst–Planck system of equations, a physics model for the IPMC sensor was proposed. For this study, experimental apparatus was developed to conduct hydrodynamic experiments for both the underwater vehicle and the IPMC sensors. By comparing the experimental and theoretical results, the speed of the underwater vehicle and the output of the IPMC sensors were well predicted by the theoretical models. A maximum speed of 1.08 × 10 −1 m s −1 was recorded experimentally at a wave frequency of 1.6 Hz. The peak output voltage of the IPMC sensor was 2.27 × 10 −4 V, recorded at 0.8 Hz. It was found that the speed of the underwater vehicle increased as the wave frequency increased and the IPMC output decreased as the wave frequency increased. Further, the energy harvesting capabilities of the underwater vehicle hosting the IPMCs were tested. A maximum power of 9.50 × 10 −10 W was recorded at 1.6 Hz.